Government Collaboration in Improving Branding of Tangkit Village Pineapple Agrowism as an Effort to Improve the Quality of Tourism Post Covid-19 Pandemic - Yarni, Meri; Hapsa, Hapsa; Suhendri, Suhendri (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2023)
Government collaboration with various stakeholders including the academic world is very relevant in exploring contemporary issues that occur in the community, including in increasing appropriate tourist destination branding to improve a positive image and be more widely known by the general public so that it can affect the number of visitors and the quality of pineapple agrotourism management in Tangkit Village, Muara Jambi Regency, by involving local governments local and students of Government Science Jambi University, The method used is descriptive qualitative, by exploring and formulating findings on the results of interviews conducted. The team has carried out planning and analysis levels by presenting solutions related to the right destination branding and can be a consideration for all stakeholders involved together to focus on improving the quality of agrotourism governance with routine, measurable, and consistent destination branding intensity. Thus this method is designed to shape the mindset of all stakeholders with conceptual, procedural, and exploratory knowledge possessed to achieve tourism governance goals with a high level of efficiency.